Hyperon global polarization in isobar Ru+Ru and Zr+Zr collisions at sNN=200GeV - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2025)
The polarization of Λ , Λ ¯ , Ξ − , and Ξ ¯ + hyperons along the angular momentum of the system has been measured in isobar collisions of Ru+Ru and Zr+Zr at s N N = 200 GeV with the STAR detector at RHIC. The polarization dependence on collision centrality exhibits an increasing trend in more peripheral collisions. Λ and Λ ¯ polarization dependence on the transverse momentum and pseudorapidity have been investigated, but no significant dependence was observed. The polarizations of Λ and Λ ¯ are found to be consistent with each other, indicating little contribution of the spin-magnetic coupling to the measured polarization. Comparison to previously measured polarization in Au+Au collisions show no obvious system size dependence. The results are qualitatively consistent with hydrodynamic calculations including contributions from shear-induced polarization and thermal vorticity. For the first time in heavy-ion collisions, the dependence of the global polarization on the hyperon’s emission azimuthal angle relative to the second-order event plane has been measured, indicating stronger polarization for the in-plane emitted hyperons at the level of 2.4 σ significance in 20–50 % centrality. The Ξ hyperon polarization measurements via polarization transfer analysis yield finite positive values with 2.9 σ significance in 20–50 % centrality, slightly larger compared to the inclusive Λ polarization. © 2025 The Authors.
Keywords: Global polarization; Hyperon; Vorticity; dept.phy